The population pharmacokinetics of dolutegravir co‐administered with rifampicin in Thai people living with HIV: Assessment of alternative dosing regimens - Baralee Punyawudho; Anan Chanruang; Thornthun Ueaphongsukkit; Sivaporn Gatechompol; Sasiwimol Ubolyam; Yong Soon Cho; Jae Gook Shin; Anchalee Avihingsanon (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Tuberculosis is the most common opportunistic infection in individuals with HIV, and rifampicin is crucial in the treatment of tuberculosis. Drug–drug interactions complicate the use of DTG in HIV/TB co‐infection, which makes drug administration more difficult. This study aimed to develop the population pharmacokinetic model of DTG when co‐administered with rifampicin. The developed model was further used to investigate different dosing regimens. Forty HIV/TB‐co‐infected participants receiving DTG 50 mg once daily (OD) with food or DTG 50 mg twice daily (b.i.d.) without food were included in the analysis. Intensive pharmacokinetic samples were collected. The data were analyzed using a nonlinear mixed‐effects modeling approach. A total of 332 DTG concentrations from 40 PLWH were analyzed. The pharmacokinetics of DTG co‐administered with rifampicin can be best described by a one‐compartment model with first‐order absorption (incorporating lag time) and elimination. Total bilirubin was the only covariate that significantly affected CL/F. DTG 50 mg b.i.d. results in the highest proportion of individuals achieving in vitro IC90 of 0.064 mg/L and in vivo EC90 of 0.3 mg/L, while more than 90% of individuals receiving DTG 100 mg OD would achieve the in vitro IC90 target. Therefore, DTG 100 mg OD could serve as an alternative regimen by minimizing the difficulty of drug administration. However, its clinical efficacy requires additional evaluation.